On the electromechanical coupling in rotordynamics of electrical machines. Issue 1 (15th March 2018) - Boy, Felix; Hetzler, Hartmut
Abstract: In this contribution the modelling of electromechanical interactions in electrical machines is revised and analysed. Based on Lagrange's equations of the second kind, approaches from literature are classified concerning the coupling between mechanical motion and electrical system behaviour. It is shown, that the modelling has a significant influence on the assessment of oscillations. This circumstance is shown investigating self‐excited oscillations in a 2‐pole asynchronous machine. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)